The Khmer Lands of Vietnam : Environment, Cosmology, and Sovereignty - Taylor, Philip, 1962- (Book collections on Project MUSE., 2014)
The indigenous people of southern Vietnam, known as the Khmer Krom, occupy territory over which Vietnam and Cambodia have competing claims. Regarded with ambivalence and suspicion by nationalists in both countries, these in-between people have their own claims on the place where they live and a unique perspective on history and sovereignty in their heavily contested homelands. To cope with wars, environmental re-engineering and nation-building, the Khmer Krom have selectively engaged with the outside world in addition to drawing upon local resources and self-help networks. This groundbreaking book reveals the sophisticated ecological repertoire deployed by the Khmer Krom to deal with a complex river delta, and charts their diverse adaptations to a changing environment. In addition, it provides an ethnographically grounded exposition of Khmer mythic thought that shows how the Khmer Krom position themselves within a landscape imbued with life-sustaining potential, magical sovereign power and cosmological significance. Offering a new environmental history of the Mekong River delta this book is the first to explore southern Vietnam through the eyes of its indigenous Khmer residents.